Plants and Geographical Names in Croatia - Čargonja, Hrvoje (Array, 2008)
The main purpose of this paper is to present some general observations, regularities and insights into a complex relationship between plants and people through symbolic systems like geographical names on the territory of Croatia. The basic sources of data for this research were maps from atlas of Croatia1 of the scale 1:100000. Five groups of maps or areas were selected in order to represent main Croatian phytogeographic regions. A selection of toponyms from each of the map was made in which the name for a plant in Croatian language was recognized (phytotoponyms). Results showed that of all plant names recognized in geographical names the most represented are trees, and among them birch and oak the most. Furthermore, an attempt was made to explain the presence of the most represented plant species in the phytotoponyms in the light of general phytogeographical and sociocultural differences and similarities of comparing areas. The findings confirm an expectation that the genera of climazonal vegetation of particular area are the most represented among the phytotoponyms. Nevertheless, there are ample examples where representation of a plant name in the names of human environment can only be ascribed to ethno-linguistic and socio-cultural motives. Despite the reductionist character of applied methodology, this research also points out some advantages of this approach for ethnobotanic and ethnolinguistic studies of greater areas of human environment.